Monologion - von Canterbury, Anselm (frommann-holzboog Verlag, 1964)
The ‹Monologion‹ deals with God, his being, his nature and his forms. It is the first real theodicy, whose audacity consists of the attempt to bring forth arguments based on considerations of reason alone. The multiplicity of evidence which he discovered then caused Anselm to search for one single argument which he developed in the ‹Proslogion‹. Anselm‹s most famous work contains the ontological proof of God‹s existence. Based on this, the ‹father of scholasticism‹ ignited a discussion which was passed on from Thomas to Hegel and even further. The dialogue ‹De veritate‹ is actually the first monograph with this title. Anselm‹s designation of truth as »rectitude which can only be determined by reason» makes it possible to perceive the unity of the logical, the ontological and the ethical, the source on which this thinking draws.